Effects of Planting Pattern on The Performance of Soybean Genotypes - Pratiwi, Herdina; Sundari, Titik (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2018)
Plant population is one of key factors in crops yield. The determination of optimum population per area unit needs to be accommodated through the planting space arrangement. This study aimed to know the performance of some soybean genotypes planted with both single and double row planting pattern. The research was conducted in Kendalpayak Experimental Field, Malang from February to May 2017 arranged in split plot experimental design with three replications. The main plot was planting space consisting of single row (40 cm x 15 cm) and double row (60 cm x 20 cm x 15 cm), while the sub-plot was the soybean genotypes consisting of 12 promising lines (Grob/IT-7-7, Grob/Pander-397-6, Grob/IT-17-1, IBK/Argop-276-3, Grob/Pander-395-2, Grob/Pander-428-1, Grob/IT-7-5, Grob/IT-7-2, Grob/IAC-453-7, IBK/ Grob-296-10, Grob/IT-7-3, and Grob/IT-7-1) and 3 cultivars as comparison (Dena 1, Dena 2, and Grobogan). Each experimental unit was set in an area of 10.8 m2. Observation was performed on variables of plant height, number of fertile nodes, number of pods with three seeds, number of pods with two seeds, number of sterile pods, seeds dry weight, pod shells dry weight, weight of 100 seeds, and yields. The results of the research showed that each genotype performed different response to planting space depending on the characteristic of it. Yield obtained from double row planting space was 4.76% higher than that from single row planting space. There were 8 genotypes (Grob/IT-7-7, Grob/Pander-397-6, Dena 1, Grob/IT-7-5, Grob/IT-7-2, Grob/IAC-453-7, Grob/IT-7-3, and Grob/IT-7-1) which were able to produce seeds 2.0 ton/ha, either planted in single row or double row planting space.